The changes in housing of the ex-Deutschland Democratic Republic from the reunification time (Ciudades, 2018)
The reunification treaty, by which, the union of both Germanys was made marked, among many other things, the general lines in the transformation of the former East Germany housing stock as to, what the possession regime refers, as to what is relating to the physical conditions of the buildings. Since them, a large number of houses has changed their owners and has been the object of a great number of improvements, producing a huge change that has been directed towards the dissolution of their public status, and naturally to their privatization. In addition to all these factors, a very important movement of population was produced, from the east to the west, provoking at the same time the show up of a very high percentage of empty houses in some specific areas of the Ex-DDR.
Keywords: East and West Germany housing owning regime; changes in the owning regime in the ex DDR; works of improvement and rehabilitation in houses; demolition of apartments; urban reforms; urban shrinking